THE DISPLACEMENT OF ACADEMICS AND ITS RELATIONSHIP WITH THE HELPLESSNESS - Estácio Neto, Francisco; de Araujo Gouvea Estacio, Gisele; de Sá Britto Silveira, Jordana (LINKSCIENCEPLACE, 2026)
The academic work seeks to identify the changes undergone in postmodernity and how these influence the subject, being the represented subject by academical who moved to Campos dos Goytacazes-RJ to continue his studies, beyond the interference of the “society of the spectacle”, “net modernity” and capitalism. The focus is on the changes undergone by the individual due to a new structure that is inserted and how identities are constructed after living together with new people, groups and places. This change of locality and separation the familiar can generate the helplessness. Using a methodology qualitative-quantitative for the analysis of interviews, besides a bibliographical approach, to understand the helplessness and the changes that university life generates.